Occupational therapy synergy between Comprehensive Community Based Rehabilitation Tanzania and Heifer International to reduce poverty - Anne Marie W. Hansen; Albert P. Chaki; Ruth Mlay (African Journal of Disability, 2013)
Background: This article describes a partnership between a community-based rehabilitation organisation and a non-governmental organisation (NGO) in Tanzania. The partnership focused on income-generating (IG) activities to tackle the problems of poverty faced by families with a child with a disability (CWD). Objectives: The aim of this case study was to describe the partnership between Comprehensive Community Based Rehabilitation Tanzania in Moshi (CCBRT-Moshi), a non-governmental organisation, and families to create an income-generating business, namely raising goats.